Answer:
The answer is A.(-4,3)
Explanation:
Multiply the first equation by -3,and multiply the second equation by 1.
−3(x+y=−1)
1(3x−4y=−24)
Becomes:
−3x−3y=3
3x−4y=−24
Add these equations to eliminate x:
−7y=−21
Then solve−7y=−21for y:
−7y=−21
![(-7y)/(-7) =(-21)/(-7)](https://img.qammunity.org/2021/formulas/mathematics/high-school/hr9sc0qwa9pe53s7nugtbf27doptpckmof.png)
y=3
Now that we've found y let's plug it back in to solve for x.
Heres our original equation
x+y=−1
Substitute 3 for y in x+y=−1:
x+3=−1
x+3+−3=−1+−3(Add -3 to both sides)
x=-4